1997
DOI: 10.1038/386495a0
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation and reactivation of somatosensory cortex after dorsal spinal cord injury

Abstract: Sensory stimuli to the body are conveyed by the spinal cord to the primary somatosensory cortex. It has long been thought that dorsal column afferents of the spinal cord represent the main pathway for these signals, but the physiological and behavioural consequences of cutting the dorsal column have been reported to range from mild and transitory to marked. We have re-examined this issue by sectioning the dorsal columns in the cervical region and recording the responses to hand stimulation in the contralateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
193
1
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 194 publications
(230 citation statements)
references
References 24 publications
30
193
1
6
Order By: Relevance
“…The lesions at cervical levels (C3-4 or C5) sectioned all or most ascending somatosensory afferents from the forelimb, and afferents from the lower body (3,(10)(11)(12). As expected, few neurons in contralateral somatosensory cortex (area 3b) were activated by tactile stimulation of the hand, and the somatotopy was grossly abnormal, as reported previously by Jain et al (7,13,14). Microstimulation results from M1 were obtained by stimulating in long microelectrode penetrations down the cortex of the anterior bank of the central sulcus, or from M1 on the brain surface at depths of ∼1.8 mm (Fig.…”
Section: Resultssupporting
confidence: 57%
“…The lesions at cervical levels (C3-4 or C5) sectioned all or most ascending somatosensory afferents from the forelimb, and afferents from the lower body (3,(10)(11)(12). As expected, few neurons in contralateral somatosensory cortex (area 3b) were activated by tactile stimulation of the hand, and the somatotopy was grossly abnormal, as reported previously by Jain et al (7,13,14). Microstimulation results from M1 were obtained by stimulating in long microelectrode penetrations down the cortex of the anterior bank of the central sulcus, or from M1 on the brain surface at depths of ∼1.8 mm (Fig.…”
Section: Resultssupporting
confidence: 57%
“…Data from other laboratories show, for example, that sprouting of spared primary afferents did not occur within the rat gracile nuclei between 5 days and 3 months after incomplete thoracic spinal cord dorsal column injury (Jain et al, 1995) nor within the non-human primate cuneate nuclei 5 days after incomplete cervical spinal cord dorsal column injury (Jain et al, 1997). Conditioning sciatic nerve injury to increase regenerative capacity (Richardson and Issa, 1984) failed to promote sprouting of spared primary afferents in the rat gracile nuclei during the first week after contusive thoracic SCI (Baker and Hagg, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, recovery of hindlimb placing was associated with axon sprouting. Additionally, Jain et al [27] observed that complete lesions of the primate cervical spinal cord dorsal columns deactivated the forelimb, trunk, and hind limb representations in the somatosensory cortex. Afferents from the face reactivated these deactivated representations.…”
Section: Spontaneous Functional Return and Recovery After Scimentioning
confidence: 99%
“…Associated with this was sprouting of trigeminal primary afferents into the brainstem cuneate nuclei, the target of forelimb and other upper extremity primary afferents [28]. Incomplete lesions of the dorsal columns led to sprouting of spared forelimb primary afferents in the cuneate nuclei and reactivation of forelimb representations [24,27]. In contrast, reactivation of hind limb representations in the rat somatosensory cortex did not occur following incomplete lesions of the thoracic spinal cord dorsal columns [29].…”
Section: Spontaneous Functional Return and Recovery After Scimentioning
confidence: 99%